The Relationship between Stroke Patients Characteristics and Family Support with Compliance Rehabilitation - Wardhani, Irma Okta; Martini, Santi (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTStroke is a cerebrovascular disease, it is brain function disorders associated with the disease of the blood vessels that supply the brain. The impact of stroke is paralysis. Family support is things that are needed to be considered in the treatment of stroke patients. It is very involved in the compliance rehabilitation of patients to prevent the re-occurrence of stroke. Characteristics of stroke patients may also affect the compliance rehabilitation. The purpose of this research is to determine the relationship between stroke patients characteristics and family support to compliance rehabilitation at the Medical Rehabilitation Unit RSU Haji Surabaya. This research was an analytic observational research with cross sectional design. The subjects of this research are taken using total population technique. The independent variables in this research is family support. The dependent variable is compliance rehabilitation. The results of this research are presented in the form of frequency distributions and calculate the strength of the relationship with Phi coefficient. The result of this research shows that there is a strong relationship between family support and compliance rehabilitation (r=0.582). There are weak relationship between ages (r=-0,027), gender (r=0,092), level of education (r= -0,295), work (r=0,098), and marital status (r=0,319). The conclusion is family support may affect compliance rehabilitation of stroke patients. It is recommended for health workers to provide counseling to improve family support in curing stroke patients.Keywords: depression, family support, compliance rehabilitation